FLIPPED CLASSROOMS IN EFL LISTENING INSTRUCTION: A SYSTEMATIC LITERATURE REVIEW - Wei , Lanlan; Said, Noraini; Ting , Pick Dew (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study presents a systematic review of empirical studies on the flipped classroom (FC) approach in English as a Foreign Language (EFL) listening instruction, with the goal of identifying current research trends, instructional activities, and the reported benefits and challenges. Following the PSALSAR framework and PRISMA guidelines, 34 empirical studies published between 2012 and October 2025 were idenified from Google Scholar, Scopus, and ERIC databases. The findings reveal that research on flipped EFL listening instruction has grown steadily since 2019, peaking in 2022. Most studies were conducted in developing countries such as Iran, Indonesia and Egypt, with undergraduate students as participants. Quasi-experimental or mixed-methods designs were predominantly employed in these studies. The review also indicates that video watching, online exercises, and note-taking are among the most-reported pre-class activities, while group discussions, skill-based tasks, and collaborative learning are among the in-class activities. What’s more, key benefits of the flipped listening instruction such as improved listening comprehension, greater learner autonomy, and increased active learning have been most frequently reported. Reported challenges, on the other hand, include technical difficulties, increased student workload and need for teacher guidance. This paper provides practical guidance for policymakers, instructors, and learners seeking to optimize FC practices in EFL listening.